Link and Match Policy to Increase Labor Absorption in Aceh: An Evaluation of Educational Policy - Muhammad Hulaimi; Sudji Munadi; Rahmat Kurniawan; Amirul Haq RD (Jurnal Penelitian Pendidikan IPA, 2024)
Education is crucial to national growth. Hence, a Link and Match program to provide work-oriented education is needed. This study uses the CIPP Model to assess the link and match policy between vocational high schools (SMK) and business and industry (DUDI). Four vocational schools located in Banda Aceh and Aceh Besar were studied. Data was acquired through expert-validated questionnaires and observation interviews. Quantitative descriptive analysis was used. The research results show that the link and match policy between SMK and DUDI has been appropriate, with an average score of four categories with appropriate criteria for each aspect. However, the implementation process is still hampered because the Aceh Government has not yet prepared a planned and measurable plan in the Strategic Plan for developing vocational education in Aceh to link and match to a vocational education master plan for long-term educational development. As a relevant stakeholder, the Aceh Education Service should clearly state the concept and measurable targets for developing links and matches in vocational schools, including what programs must be prepared to address the strategic issue of strengthening links and matches, especially in vocational schools with DUDI, to meet needs.